Triboelectrification of Pharmaceutical powders: A critical review - M. Usman Ghori; Barbara Conway (University of Huddersfield Press, 2018)
The majority of pharmaceutical and polymer powders are insulating materials that have the propensity to attain and then retain triboelectric charge. This phenomenon can potentially give rise to issues during handling and processing of materials. A comprehensive understanding of the mechanisms controlling charging behaviour can inform effective control of the process and potentially enhance the final product quality and performance. Therefore, the objective of this review article is to summarise the principles of triboelectric charging and to understand the various contributing factors. It is intuitively expected that the acquired understanding can be helpful in improving the efficiency, quality, performance and safety of powder processing phenomena and final products.